Suggested Technique for Creating Physical Growth Curves Charts for Anthropometric Measurements in Admixed form in a sample of children under two years of age In Diyala Governorate - Al-Naqeeb, Abdul Khaleq; Abdul Sattar, Khalida; Noaman, aqeel (Iraqi National Journal of Nursing Specialties, 2012)
Objective: This study aimed to assessing new suggested technique of Physical Growth Curves (PGC) charts in children under two years old of a non-probability sample. Methodology: A non-probability sample of size (420) children under two years selected from 12 Primary Health Care Centers in Diyala governorate during the period from 15th Nov. 2010 to 13th Mar. 2011 according to admix of a different properties together in one chart/or growth curve chart included in at least weight, Height, and Head circumference. Results: the results showed different properties that can be admix together in one chart/or growth curve chart included in at least weight, Height, and Head circumference. And to overtake the problem of the normal distribution assumption that ought to be presented with the random variables of (PGC) in applying the conventional methods. Obtaining or estimating the (min. and max.) of the standard limits as well as the trimmed mean which were accredited on their original observations which were collected from the studied field. Recommendations: Continuous to apply the suggested technique in added another physical body’s properties such as (MUAC, Trunk Length related to abdomen center).